Abolition of the fast track of lysozyme folding at neutral pH - Texter, F; Coyle, J; Kulkarni, S; Robinson, C; Radford, SE (1997)
Studies in this laboratory have shown nat [he reLozolng of lysozyme is accelerated in the presence of equimolar GroEL. We are now investigating the molecular origin of this rate enchancement. The conditions under which the rate enhancement occurs are pH 7.2, 400 mM KCI, and GroEL. The first step in this study is a reexamination of the folding mechanism of lysozyme under these conditions in the absence of GroEL. Here we present the folding pathway of ivsozvme under these conditions determined using fluorescence, circular dichroism, hydrogen exchange labeling. IH-NMR, and electrospray ionization mass spectrometry (ESI-MS). We show that under these conditions the fast track folding is no longer populated, but that folding still occurs along parallel pathways. (This work was carried out while FLT was on sabbatical leave at te Universities of Oxford and Leeds, supported by an Albright College Sabbatical Grant. The work was supported by grants from BBSRC, MRS, The Roya] Society and The Wellcome Trust.).